Efektifitas sinar ultraviolet terhadap cemaran bakteri patogen pada makanan cair sonde untuk pasien immune-compremissed - Sulatri, Ni Luh; Yogeswara, Ida Bagus Agung; Nursini, Ni Wayan (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : Food safety remained as critical concern to immune-compremissed patient. Food safety assurance can be achieved through inhibition of pathogenic bacteria by physical treatment such as UV light radiation. However, a study regarding the effect of UV light on growth of pathogenic bacteria in contaminated liquid food are scarce.Objective : To determine the effectiveness of UV light on contamination of pathogenic bacteria in liquid food for immune-compremissed patient.Methods : Randomized design with two factor which were holding time for 60 and 120 minutes and radiation exposure (0, 5, 10 and 15 minutes). The data was analyzed using ANOVA Result : The viscosity and pH of liquid foods were 20 centipoise and 7,15 respectively. Radiation of UV light on contaminated food that have been incubated for 60 and 120 minutes at 37oC showed significant increase (1-2 log cycle) on growth of pathogenic bacteria.Conclusion : Radiation of UV light on contaminated liquid food were not effective to inhibit or kill pathogenic bacteria during holding time (60 and 120 minutes).